Transhumanizm: kilka uwag na temat filozoficznych źródeł sporu o ideę biomedycznego ulepszania moralnego - Soniewicka, Marta (ETHICS IN PROGRESS, 2015)
The paper addresses the problem of the philosophical sources of the debate over moral human enhancement held between transhumanists and bio-conservatives. The paper is aimed at showing that the opposing positions in the debate are grounded in different philosophical traditions, namely naturalistic (Darwinian) and rationalistic (Kantian), which define human nature differently. Morality and moral improvement are also differently understood in these different traditions, thus the assumptions rooted in them lead to different conclusions concerning the idea of human moral enhancement and its justification.